THE FAMILY LEARNING APPROACH: A CONCEPT NOTE - Dumond, Marine (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2019)
The family learning approach, home education, or homeschooling is an alternative pedagogical choice that enables parents to take charge of their school-aged child’s education by replacing full-time school attendance. Scientific research on the family learning approach is emerging and mainly conducted and published in English-speaking contexts. This article presents a brief concept note of recent and international scientific literature on the family learning approach in order to identify studied dimensions and current knowledge. The following themes are addressed: history, current picture, place in society, and issues of the family learning approach.